Strategi Digital Marketing untuk Meningkatkan Promosi dan Penjualan Produk Kopi Lokal Karang Sidemen, Lombok Tengah - Nur Afni; Elya Antariksana Bachmida; Baiq Rien Handayani; Yuhendra AP; Hary Kurniawan; Amuddin Amuddin; Sukmawaty Sukmawaty; Ince Siti Wardatullatifah S; Isnaini Puspitasari; Hanifah Ayu; Fakhrul Irfan Khalil; Fuad Sauqi Isnain; Murad, Murad; Joko Sumarsono; Satrijo Saloko; Reza Kusuma Nurrohman; Diah Ajeng Setiawati; Rahmat Sabani; Wayan Sweca Yasa; Firman Fajar Perdana; M.Azhar Mustafid; Mi’raj Fuadi; Tri Isti Rahayu; Neyla Vista Maramy; Wiwin Apriyanditra; Zulfiana Jayanti; Saparudin Saparudin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Local coffee micro, small, and medium enterprises (MSMEs) in Karang Sidemen Village, Central Lombok Regency, have significant development potential; however, they still face challenges related to marketing practices and limited value addition. Conventional marketing systems restrict market reach and reduce product competitiveness. In the context of the Industrial Revolution 4.0 and Society 5.0, digital marketing offers a strategic opportunity for MSMEs to enhance product promotion and sales performance. This community service program aimed to strengthen the capacity of local coffee MSMEs through the implementation of social media–based digital marketing strategies. A participatory approach was employed, actively involving MSME actors and students through stages of problem identification, program planning, training and hands-on digital marketing practices, and evaluation. The results demonstrated an improvement in participants’ understanding and skills in utilizing social media as a promotional tool, as reflected by the initiative to develop and publish promotional video content for local coffee products, including the flagship Versilia coffee variant. The use of visual content and storytelling facilitated the practical adoption of digital marketing strategies. Overall, this program contributed to shifting marketing behavior from conventional to digital approaches and strengthening the sustainable competitiveness of local coffee MSMEs.